2010
DOI: 10.1111/j.1467-8551.2010.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Indian Micromultinationals

Abstract: ‘Micromultinationals’ are small to medium‐sized enterprises (SMEs) that use higher‐commitment entry modes beyond exporting. The study extends the micromultinational notion by addressing the question: what enables some internationalizing SMEs to become micromultinationals rather than pure exporters? Adopting a connectionist and bonding perspective, its focus is on cross‐border coethnic ties as a valuable source of social capital. A survey of 102 Indian software SMEs indicates that higher stocks of cross‐border … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 84 publications
(190 reference statements)
3
64
0
1
Order By: Relevance
“…However, the current model lends support to theoretical considerations and empirical findings from previous studies (e.g. Zahra et al, 2008 experience, and ability to work in different economic systems (Prashantham, 2011;Prashantham & Dhanaraj, 2010). In such circumstances family commitment culture could have a positive relationship with degree of internationalisation as their families might be spread out throughout the world and their businesses might follow suit.…”
Section: Limitations and Future Researchsupporting
confidence: 77%
“…However, the current model lends support to theoretical considerations and empirical findings from previous studies (e.g. Zahra et al, 2008 experience, and ability to work in different economic systems (Prashantham, 2011;Prashantham & Dhanaraj, 2010). In such circumstances family commitment culture could have a positive relationship with degree of internationalisation as their families might be spread out throughout the world and their businesses might follow suit.…”
Section: Limitations and Future Researchsupporting
confidence: 77%
“…Entry mode studies investigate the antecedents and consequences of a firm's choices posed by possible arrangements for participating in a foreign market [Hennart, 2014]. Despite a large body of literature, some gaps remain, including analyses of the modes of entry chosen by SMEs [Prashantham, 2011]. More specifically, the majority of studies on SME internationalisation focus on exporting.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Dimitratos et al [2014], relying on a sample of 116 internationalized Chilean SMEs, found that networking (with both domestic and international partners), as well as risk-taking propensity, increased the probability of a firm becoming a mMNE. Prashantham [2011], using data from 102 Indian software firms concluded that cross-border co-ethnic ties increase the likelihood that a SME become a mMNE, and that mMNEs have a significantly higher level of internationalisation (measured with the foreign sales to total sales ratio) than exporters.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Social networks are important in the internationalization process of both large and small firms (Chetty and Blankenburg Holm, 2000). The advantages embedded in social ties are often referred to as social capital which can be considered TEs' most effective resource (Acquaah, 2007;Prashantham, 2011). Social embeddedness is defined as "the density and strength" of an immigrant's social ties within their local ethnic community and their homeland (Nielsen and Riddle, 2007, p. 5).…”
Section: 1mentioning
confidence: 99%